Study of 5.8 GHz Band-Stop Frequency Selective Surface (FSS) - Hong, T.Y.; Lee, Y.S.; Wee, F.H.; You, Y. K.; A. Karim, M.N.; Ramli, N. H.; Gan, Hong-Seng; Jamlos, M.A. (International Journal of Integrated Engineering, 2019)
This paper presents the study of 5.8 GHz frequency selective surface (FSS) acts as a band stop to eliminate unwanted radiation signal at 5.8GHz. The FSS was designed using computer simulation technology (CST) Microwave Studio software. The paper shows the comparison of square loop, octagon loop and hexagon loop of Band stop FSS (BSFSS) performance at 5.8 GHz. Besides, the BSFSS design using four different type of dielectric substrate such as FR-4, TLY-5, Roger RT5870 and Roger RT5880 were compared. The results obviously show that the Rogers RY5880 has the attenuation -44.72 dB.  The fabricated FSS were measured by using free space technique with two horn antennas connected to performance network analyzer (PNA). The measured and simulated results were compared. The results show that the square loop FSS structure have the better attenuation -26.76 dB (simulated) and -38.34 dB (measured) at 5.8 GHz.